Swat State (1915-1969) From Genesis to Merger : An Analysis of Political, Administrative, Socio-Political, and Economic Development - Sultan-i-Rome (Karachi, Pakistan Oxford University Press, 2008)
"The book discusses the nomenclature, geography, climate and natural vegetation, regional ethnicity and lineages and historical perspective of Swat, Pakistan. It evaluates and analyzes the genesis of the once Princely State of Swat in the historical, geo-political and strategic context. It deals with the consolidation and expansion of the former State holistically. Moreover, it evaluates the State's relations with the British Government and later Pakistan, and with the neighboring states of Dir and Amb. The book evaluates and analyzes the administrative system including the civil, military, financial and judicial spheres. It also deals with the socio-cultural milieu and changes brought about in Swat in respect of education, language, religion, health, permanent settlement, communication, trade and industry, agriculture, tourism, leadership, and women's rights. It looks at the merger of the former state into Pakistan, the constitutional status of the State, causes of the merger, the Wali's role in the merger, and both positive and negative effects and impacts of the merger."--Jacket.
Include Index, Glossary and Colour Illustration
Keywords: Pakistan--Swāt District -- Politics and government